Pengaruh Experiential Marketing terhadap Customer Loyality Starbucks Coffe dengan Customer Engagement sebagai Variable Intervening - Fandi Pratama Putra; Siti Mujanah; Achmad Yanu Alif Fianto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to analyze the impAct of Experiential Marketing on Customer Loyalty with Customer Engagement as an intervening variable at Starbucks Coffe - Surabaya. Data collection was conducted through direct and online surveys via social media. The total number of respondents was 100 with the criteria of customers who have visited and transActed at least one time in the last one month. The tools used for data processing are Partial Least Square (PLS-SEM) techniques. The results of this study indicate that Experiential Marketing has a positive significant effect on Customer Loyalty, Experiential Marketing has a positive significant effect on Customer Engagement, Customer Engagement has a positive significant effect on Customer Loyalty, and Customer Engagement intervenes significantly between Experiential Marketing and Customer Loyalty.